(untitled) (Scientific journal of the Fergana State University, 2024)
In the article, the process of improving the synchronicity of the movements of female athletes in synchronized swimming, the issues of coordinating and controlling the rhythm and tempo of the competition program based on a new approach with the help of information technologies are highlighted. At the same time, by creating the SINXRO computer program, he implemented a new technology that enables the optimization of the rhythm and tempo of movements of synchronized swimmers during training and competition processes, and allows athletes to avoid low strength, low time, and injuries